Base-Catalyzed Polymerization of a Substituted Methylenebicyclo[3.3.1]nonane - Sujeet Kumar Thakur; Seera Raviteja; Tayur N. Guru Row; Sambasivan Venkat Eswaran (International Journal of Polymer Science)
Lignite humic acid on reaction with formaldehyde and aqueous alkali led to a polybicyclo[3.3.1]nonane. This was characterized spectroscopically using mass spectrometry, FT-IR, powder X-ray diffraction, TEM, and NMR studies (1H-NMR, CP-MAS-SS-NMR) which though challenging were useful for confirming the structure of the BCN polymer. The product showed an envelope peak in its MALDI-MS spectrum, based on which M̅n, M̅w, and polydispersity index have been calculated. Based on the NMR spectrum of intermediate, the presence of the N-formyl group has been shown in it. The new polymer could be useful in agriculture in water-deficient areas. Most papers on humic acids include only broad and general information like elemental analysis (occasionally TEM, SEM, TGA, DSC, etc.). Very complicated structures have been proposed by scientists earlier. Only in very recent years, it has been recognized that these are relatively small molecules which masquerade as supramolecular structures. It is pointed out that most papers do not put down the structure of the compound and provide no concrete proof for proposing such structures. The novelty of our work is that we have characterized the precise molecular weights based on mass spectrometry and NMR spectroscopy along with a well-defined structure. This is not the case in most other publications.